Bleached mudstone, iron concretions, and calcite veins: a natural analogue for the effects of reducing CO2‐bearing fluids on migration and mineralization of iron, sealing properties, and composition of mudstone cap rocks. Issue 5 (21st November 2016) - Ming, X. R.; Liu, L.; Yu, M.; Bai, H. G.; Yu, L.; Peng, X. L.; Yang, T. H.
Abstract: This study investigates the Wangfu Depression of the Songliao Basin, China, as a natural analogue site for Fe migration (bleaching) and mineralization (formation of iron concretions) caused by reducing CO2 ‐bearing fluids that leak along fractures after carbon capture, utilization, and storage. We also examined the origin of fracture‐filling calcite veins, the properties of self‐sealing fluids, the influence of fluids on the compositions of mudstone and established a bleaching model for the study area. Our results show that iron concretions are the oxidative products of precursor minerals (pyrite and siderite) during uplift and are linked to H2 S and CO2 present in early stage fluids. The precipitation of calcite veins is the result of CO2 degassing and is related to CO2, CH4, and minor heavy hydrocarbons in the main bleaching fluids. In our model, fluids preferentially enter high‐permeability fracture systems and result in the bleaching of surrounding rocks and precipitation of calcite veins. The infilling of calcite veins significantly decreases the permeability of fractures and forces the fluids to slowly enter and bleach the mudstone rocks. The Fe 2+ released during bleaching migrates to elsewhere with the solutions or is reprecipitated in the calcite veins and iron concretions. The formation of calcite veins reduces the fracture space and effectively prevents fluid flow. The fluids have an insignificant effect on minerals within the mudstone. In terms of the chemistry of the mudstone, only the contents of Fe2 O3, U, and Mo change significantly, with the content of U increasing in the mudstone and the contents of Fe2 O3 and Mo decreasing during bleaching.